IMPLEMENTASI DASAR PUBLIC SPEAKING KEPADA ANAK- ANAK PANTI ASUHAN NURUL JANNAH UNTUK MENINGKATKAN KEPERCAYAAN DIRI - Azeharie, Suzy; Christina; Kambey, Alannys Zefanya; Chang, Keith Prasethio; Thommy; Mckanzie, Yoel (Jurnal Serina Abdimas, 2024)
Public Speaking is one of the activities of a speaker when speaking in public to convey information, news, and messages to the audience or people who listen. Public speaking is not born by itself but needs to be trained to be a good speaker through the direction of others who are more expert. Everyone who has the ability to speak can learn and improve their abilities in terms of public speaking because basically public speaking is just talking directionally. Young people's awareness is very lacking about the importance of public speaking because the school system is too focused on theory rather than practice. One of them happened to the children of Nurul Jannah Orphanage, most of their children became shy if given the task to speak in front of the class or crowd. So, This PKM was held at Nurul Jannah Orphanage, that located in Malaka Road III No.84, Malaka Sari, Duren Sawit, East Jakarta. The PKM was held on September 23rd, 2023 until 3 weeks. The children of Nurul Jannah Orphanage are invited to work by listening to the tips given to be applied in life to dare to speak in public. This education is carried out by presentation and interaction methods during the course and children practice speaking in front to increase confidence, feel and apply the tips that have been shared. This education is expected to be useful and useful for the provision of the future of Indonesia's brilliant and successful young generation. The Result of This PKM was good to prove that all children are happy and educated.